2018
DOI: 10.1097/scs.0000000000004319
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression in Mothers of Infants With Cleft Lip and/or Palate

Abstract: This study describes postpartum depression rates and risk factors for mothers with infants with cleft lip and/or palate as postpartum depression has been associated with a range of negative maternal and child outcomes. A retrospective chart review from August 2009 to May 2015 included medical diagnoses, demographics, receipt of prenatal diagnosis, and the Edinburgh Postnatal Depression Scale (EPDS). Mothers (N = 206) had infants (59.2% male; mean age in weeks 5.1 ± 6.9) with isolated cleft lip (18%), cleft pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…CL/P can be repaired with craniofacial plastic surgeries [2, 4]; however, parents of infants with CL/P generally suffer from parenting and/or caregiving issues as a result of lower infant weight gain due to difficulties in direct breastfeeding and higher risk for upper respiratory infection [57]. Mothers of infants with CL/P reportedly tend to show negative moods such as depression and anxiety [8, 9]. Johns et al found a higher tendency of postpartum depression among older mothers of infants with CL/P [9].…”
Section: Introductionmentioning
confidence: 99%
“…CL/P can be repaired with craniofacial plastic surgeries [2, 4]; however, parents of infants with CL/P generally suffer from parenting and/or caregiving issues as a result of lower infant weight gain due to difficulties in direct breastfeeding and higher risk for upper respiratory infection [57]. Mothers of infants with CL/P reportedly tend to show negative moods such as depression and anxiety [8, 9]. Johns et al found a higher tendency of postpartum depression among older mothers of infants with CL/P [9].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluar el estado psicológico de las madres no era un objetivo de este trabajo, pero es un factor relevante que afecta al vínculo que éstas puedan lograr con sus hijos con FLMP, influyendo directamente en las prácticas de lactancia materna, por lo que sería interesante incluirlo en investigaciones futuras. El diagnóstico prenatal de la FLMP, puede contribuir al ajuste postparto materno positivo y no tenerlo constituye un factor de riesgo para la depresión post-parto (Johns et al, 2018).…”
Section: Discussionunclassified
“…CL/P can be repaired with craniofacial plastic surgeries [2,4]; however, parents of infants with CL/P generally suffer from parenting and/or caregiving issues as a result of lower infant weight gain due to difficulties in direct breastfeeding and higher risk for upper respiratory infection [5][6][7]. Mothers of infants with CL/P reportedly tend to show negative moods such as depression and anxiety [8,9]. Johns et al found a higher tendency of postpartum depression among older mothers of infants with CL/P [9].…”
Section: Introductionmentioning
confidence: 99%